Intercropping, Crop Diversity and Pest Management - Hugh A. Smith; Oscar E. Liburd (EDIS, 2012)
Growing different crops in the same field and/or planting different crops on the same plot during different times of the year can reduce insect pest populations, increase beneficial insects, and suppress weeds. In addition, non-crop plants such as weeds, cover crops, and habitat plantings can be combined in space and time to influence numbers of pest and beneficial arthropods on the main crop. This 7-page fact sheet was written by Hugh A. Smith and Oscar E. Liburd, and published by the UF Department of Entomology and Nematology, February 2012.